Mussolini at the wedding of his son Bruno in Rome. At the left: bride and broom. Next to them: the wife of Benito: Rachele. Text on the back
Mussolini at the wedding of his son Bruno in Rome. At the left: bride and broom. Next to them: the wife of Benito: Rachele. Text on the back.